(untitled) (Baghdad Science Journal, 2008)
The effect of nitrogen fertilizer and the planting distance on growth and yield of the sunflower cultivar (Taka) was investigated. The experiment was conducted in the field using five nitrogen fertilizer levels (0, 50, 100, 150, 200) kg/donum and three planting distances (10, 20, 30) cm/plant. The experiment design was split-plot by using RCBD with four replicates. The level of fertilizer as the main plot, while the planting distance as the sub plot. Plant high and yield components were measured. Results indicated that using 200 kg/donum of nitrogen and 30 cm/plant of planting distance gave the highest rate of 1000 seeds weight and the number of seeds/ head. While using 200 kg/donum of nitrogen fertilizer with 10 cm/plant of planting distance gave the highest fertility percentage. Also the results indicated that the interaction between the nitrogen fertilizer and planting distance was not significant in most of the characters that were measured.